Pengaruh Advertising Attractiveness, Online Costumer Review, Influencer Marketing terhadap Purchase Decision Melalui Costumer Trust Selaku Variabel Intervening (Study Kasus Pada Skincare Skintific Di Yogyakarta): STUDY KASUS PADA SKINCARE SKINTIFIC DI YOGYAKARTA - Audi Gita Nanda; Suhartono Suhartono (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This study aims to determine the effect of Advertising attractiveness, Onlie costumer review, Influencer marketing, on purchase decision throught costumer trust (Case Study on SKINTIFIC in Yogyakarta). This research uses quantitative methods. The population in this study were SKINTIFIC skincare costumers in Yogyakarta who were obtained from distributing questionnaires with samples taken using nonprobabilitu sampling method, namly sampling techniques with a census so that the sample used in study was 100 responden. The results of this study indicate that: (1) Advertsing attractiveness has a positive and significant effecr on costumer trust, (2) Online costumer reviews has a positive and significant effect on costumer trust, (3) Influencer marketing has no positive and significant effect on costumer trust, (4) Advertsing attractiveness has a positive and significant effect on purchase decision, (5) Online costumer review has a positive and significant effect on purchase decision, (6) Influencer marketing has a positive and significant effect on purchase decision, (7) Costumer trust has a positive and significant effect on purchase decision, (8) Advertising attractiveness, purchase decision, and customer trust have a positive and significant effect on each other so that they can mediate between the three, (9) Online Costumer Review, purchase decision, and customer trust do not have a positive and significant effect on each other so that they cannot mediate between the three, (10) Influencer marketing, purchase decision, and customer trust do not have a positive and significant effect on each other so that they cannot mediate between the three.